2016
DOI: 10.3354/ab00666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial scale and habitat on the diversity of diapausing wetland invertebrates

Abstract: The community structure of aquatic invertebrates producing dormant propagules has been associated with both local and regional-scale factors in temporary wetlands. We explore how patterns in the diversity of drought-resistant aquatic invertebrates are related to different spatial scales in ponds with distinct plant structural complexities. We tested 3 hypotheses: (1) the finest spatial scale (fine-scale diversity) has the strongest contribution to diversity and composition; (2) the fine-scale diversity will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Hatchlings were determined to the finest resolution possible (species or genus level, sometimes morphotypes) under a microscope (model MIC-100, S ×20-40 magnification) after consultation with specialized literature (Elmoor-Loureiro, 1997;Koste, 1978). For preservation, we transferred hatchlings to 1.5-ml polypropylene microtubes with 4% formaldehyde (Rotifera), 80% ethanol and a drop of glycerin (Ostracoda) or 80% ethanol for the other groups (Freiry et al, 2016). Hatchling samples were stored at the Laboratory of Ecology and Conservation of Aquatic Ecosystems of UNISINOS.…”
Section: Laboratory Hydrationsmentioning
confidence: 99%
“…Hatchlings were determined to the finest resolution possible (species or genus level, sometimes morphotypes) under a microscope (model MIC-100, S ×20-40 magnification) after consultation with specialized literature (Elmoor-Loureiro, 1997;Koste, 1978). For preservation, we transferred hatchlings to 1.5-ml polypropylene microtubes with 4% formaldehyde (Rotifera), 80% ethanol and a drop of glycerin (Ostracoda) or 80% ethanol for the other groups (Freiry et al, 2016). Hatchling samples were stored at the Laboratory of Ecology and Conservation of Aquatic Ecosystems of UNISINOS.…”
Section: Laboratory Hydrationsmentioning
confidence: 99%
“…Many studies have analysed the β diversity of aquatic active communities, concluding that turnover is the main factor driving differences in spatial (between pond) β diversity (Atkinson et al, 2021; Fernández‐Aláez et al, 2020; Hill et al, 2021; Korhonen et al, 2010; Martins et al, 2019), but other studies have found nestedness as the main factor driving β diversity (Florencio et al, 2011; Gleason & Rooney, 2018; Pires et al, 2017). Only a few studies have assessed the β diversity of the egg bank, and they found turnover to be the main component driving β diversity (Declerck et al, 2011; Freiry et al, 2016; Freiry, Weber, et al, 2020). However, to our knowledge, no study has compared β diversity and its components between active communities in the early stages of the hydroperiod (i.e.…”
Section: Introductionmentioning
confidence: 99%